ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦æ±‰è¯ä¸“ä¸š2014å±Šå¦ç”Ÿä½¿ç”¨â€œæ¯”â€å—å¥çš„åè¯¯åˆ†æž - Viria, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
?? ?????????????????????????????????????????????????????????????????????????????????????????????????????????, ??????????????????????????2014???????????????????????????????????????????????? ??????????52,27%???????????????????????????????????????????????????????????????   ??????????????????? Abstract Comparative sentence is a sentence that is often used in everyday life. Comparative sentence is a sentence to compare two or more things, therefore the comparative sentence should appear object and the comparison objects are compared, at the same time there must be a result of the comparison. For learners who learn Mandarin as a second language, comparative sentences in Indonesian and comparative sentences in Mandarin is not the same, so easily lead to misuse on college campuses.The author conducted research use of the phrase "bi" in 2014 the student of Chinese language education courses Tanjongpura University, analyzed the error of use and look for the cause misuse. From the research, the authors conclude that the error percentage use of the phrase "bi" in the wording error in the student class of 2014 was 52.27%. The cause of the error using the phrase "bi" in students due to receive Indonesian influence and understanding of students to different teaching materials.The author hopes that through writing this paper can provide a reference to the facultyclassroom teaching Mandarin. Keywords: ?Bi? Sentences, Error Analysis, The Cause of The Error